Roles and Responsibilities of Teachers in School Library Use - Önal, İnci and Alaca, Erdinç (Information World, 2015)
This study was carried out in order to measure the impact of the teachers in the use of the school library services by the secondary school students. Within the frame of the research, a questionnaire comprised of 16 questions were distributed to 225 students who were in the fifth, sixth, seventh and eighth degrees in Ankara, Keçiören Mustafa Necati and Ulviye Fenmen Secondary Schools with the purpose of measuring the impact of the teachers in the school library use. As a consequence it was found out that teachers of both secondary school teachers did not have a significant impact on the library use of the students, in 2014-2015. Also, untidy and neglected libraries in the schools and absence of relevant staff were observed as the other reasons of the negative attitudes of the students towards libraries.